An Outline of the History of Capsicums in England - Thick, Malcolm (Petits Propos Culinaires, 2012)
In four and a half centuries of cultivation in England, capsicums have been used as food, medicine and as decorative plants. Discovered in America by European adventurers, they have become a food well known in many parts of the world. This piece outlines their history in England, which dates from 1548, the earliest known mention in print of the cultivation of capsicums in England. However, it really took until the late 20th-century for their culinary potential to be realized by the average consumer.